A Sustainable Approach to Tensile Property Enhancement in Sand Casting Via Metal Chip–Sand Composite Molds - Isyaku, Maaruf; Yawas, Danjuma Saleh; Afolayan, Mathew Olatunde; Ause, Terva (UI Scholars Hub, 2026)
The present work focuses on the study of the effect of adding different weight percentages and particle sizes of various metal chips to foundry sand on the tensile strength of aluminum alloy castings, utilizing Taguchi's optimization methodology and regression analysis. Characterization techniques such as X-ray fluorescence (XRF), thermogravimetry, and SEM were also used. The XRF analysis identified aluminum (76.61%), silicon (17.49%), and magnesium (1.28%) as the major elements in the aluminum alloy engine block. For the foundry sand, silicon (89.51%), phosphorus (7.41%), and potassium (1.7%) were found. In contrast, the major constituents in cast iron included iron (88.3%), carbon (3.7%), and silicon (2.3%), while brass comprised primarily copper (64%), zinc (23%), and iron (3.2%). Altered composition of the molding sand improved the tensile strength by 61.05%. The optimization results show an improvement of 64.21% in the tensile strength. Thermogravimetric examination also revealed a 14.59% improvement in the thermal stability.The developed regression model for predicting tensile strength demonstrated a robust fit, with R-square values of 95.57% (R2), 93.35% (adjusted R2), and 87.64% (predicted R2). Testing of foundry attributes also showed that using brass chips with foundry sand made a significant impact, increasing the green and dry compressive strengths by 16% and 18%, respectively, and the compactability by 7% compared to the control sample. In general, the results support the idea that improving the composition of metal chips has a favourable effect on the strength, thermal, and structural properties, which in turn makes aluminum alloy castings work more effectively.